2013
DOI: 10.1364/oe.21.017060
|View full text |Cite
|
Sign up to set email alerts
|

LiF, an underestimated supercontinuum source in femtosecond transient absorption spectroscopy

Abstract: We present supercontinua generated in LiF and CaF(2) revealing that LiF is advantageous especially in the near UV region since it pushes the cut-off wavelength about 17 nm towards lower wavelengths and the occurrence of color centers, which has been considered as a drawback up to now, is not a limitation for its applicability in femtosecond transient absorption spectroscopy. Even though the color centers occur within a short time of illumination, they do not influence the supercontinuum generation significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although neglected in some studies 148 , formation of persistent color centers in LiF was generally considered as a major drawback to its application for SC generation. However, a more recent study revealed that color centers only slightly modify the ultraviolet cut-off (at 270 nm) of the SC spectrum on the long-term (several hours) operation 191 .…”
Section: Alkali Metal Fluoridesmentioning
confidence: 99%
“…Although neglected in some studies 148 , formation of persistent color centers in LiF was generally considered as a major drawback to its application for SC generation. However, a more recent study revealed that color centers only slightly modify the ultraviolet cut-off (at 270 nm) of the SC spectrum on the long-term (several hours) operation 191 .…”
Section: Alkali Metal Fluoridesmentioning
confidence: 99%
“…However, the nonlinear materials that produce the largest spectral blue shifts, LiF and CaF 2 , exhibit several drawbacks that are unattractive for practical applications. More specifically, LiF is prone to rapid formation of colour centres, which modify the SC spectrum to a certain degree [19,20]. On the other hand, optical damage in CaF 2 due to heat accumulation develops very quickly even at relatively low (1 kHz) pulse repetition rate, so the crystal should be continuously translated [21].…”
Section: Introductionmentioning
confidence: 99%